Selection for high spike fertility index increases genetic progress in grain yield and stability in bread wheat - Alonso, Maria Pía; Mirabella, Nadia. E; Panelo, Juan Sebastián; Cendoya, Maria Gabriela; Pontaroli, Ana Clara (Springer Netherlands, 2018)
Spike fertility index (SF) has been proposed as a promising trait to be used as a selection criterion in wheat breeding programs aimed at increasing grain yield, but no actual evidence of its successful application has been reported. In this study, 146 recombinant inbred lines derived from a cross between ‘Baguette 10’ and ‘Klein Chajá’, Argentinean spring bread wheat cultivars with contrasting SF, were evaluated during three crop seasons (2013, 2014 and 2015) at Balcarce, Argentina. Grain yield, grain number/m2, grain weight, and SF were measured at maturity. Changes in grain yield (i.e., responses to selection) after application of different selection strategies, including different selection criteria and selection intensities, were determined. Significant correlations were observed between grain number and grain yield, SF and grain yield, and SF and grain weight. Analysis of SF variance components showed a significant genotype × environment interaction, but it represented only 9% of the total variation, whereas 51% of the variation was genetic, resulting in a high narrow-sense heritability (0.84). The use of SF as a selection criterion, either solely or in combination with selection for high yield, increased yield, resulting in higher and more stable yields than if selecting for high yield alone. Our findings support the use of spike fertility index as a selection criterion for increasing genetic progress and stability of yield in bread wheat breeding programs.